Adolescent Developmental Psychology in the Novel Ibu yang Kusayang - Jantra, Baseni; Mohd. Hanafiah, Halis Azhan; Nik Muhamad Affendi, Nik Rafidah; Sujud, Arba’ie (Universitas Negeri Padang, 2025)
This study aims to analyse adolescent developmental psychology as portrayed in a novel. Ibu Yang Kusayang (IYK) is a novel that won the Children’s Novel Writing Competition organized by Dewan Bahasa dan Pustaka in 1978 and was published in conjunction with the International Year of the Child in 1979. This is significant due to confusion surrounding the novel’s identity. Although IYK is presented as a children’s novel, the study finds that it tends to depict its protagonist as an early teenager. The main question of this study is to identify the characteristics of adolescence portrayed in the novel. Therefore, content analysis and library research methods were used to determine the protagonist’s identity. This study sets two objectives. First, to analyse the conflicts experienced by the protagonist. Second, to identify the psychological aspects influencing adolescent development based on Erik Erikson’s theory. Erikson outlines human development in eight stages, each involving specific conflicts. This study focuses on the fifth stage “Identity vs. Role Confusion” which applies to adolescents aged 12 to 18. Thus, analysing IYK is appropriate, as although it won a children’s novel competition, the protagonist fits within the adolescent stage. The study finds that both objectives were successfully achieved and concludes that the protagonist experiences emotional conflict and identity confusion. It is hoped that this research will assist future scholars in examining the identity elements in literary works.